Successful Management of Endotipsitis: After Direct Intrahepatic Portocaval Shunt for Budd–Chiari Syndrome - Kundaragi, Nischal G.; Sakpal, Mallikarjun; Nagendra, Bhavyashree Thittamaranahalli; Asthana, Sonal (Journal of Clinical Interventional Radiology ISVIR, 2025)
We report successful management of transjugular intrahepatic portosystemic shunt stent infection (endotipsitis) following direct intrahepatic portocaval shunt for chronic Budd–Chiari syndrome. PETCT confirmed FDG-avid vegetation/thrombus within the stent graft, which was removed with a large-bore sheath aspiration technique, and the residual thrombus was excluded by placing an additional stent graft. The thrombus was positive for E. coli, and appropriate antibiotics were given. Patient improved with no recurrent symptoms during a follow-up of 7 months.
Keywords: endotipsitis; DIPS; Budd–Chiari syndrome